Biomass and lipid production from indigenous Nannochloropsis sp. by employing stress factors for improved biodiesel production - Primilla, Paramasivam; Karthiani, Kanagesan; Bhuyar, Prakash; Natanamurugaraj, Govindan; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam (Springer, 2021)
The marine microalgae Nannochloropsis sp. was grown in a different stress factor to produce maximum biomass and lipid production. The experimental stress factors were light, salinity and pH. The result showed that the maximum growth rate of Nannochloropsis sp. was observed best in photoautotrophic, the salinity of 30 ppt and pH of 8 at 25 ºC ± 1. Under the optimized conditions, biomass and lipid productivity was at 1.37 ± 0.08 g L−1 d−1 and 9.45 ± 0.96 g L−1 d−1, respectively. The fatty acids in the microalgae lipid were found to be as follows (%, w/w of total lipids) ΣMUFA74.08%, ΣPUFA 8.86% and ΣSFA 16.86%. The present study suggested Nannochloropsis sp. promising indigenous marine algae for twin uses in aquaculture as well as in biodiesel production. The dominance of unsaturated fatty acids makes the lipid from Nannochloropsis sp. one of the novel sources for biodiesel production. Unsaturated fatty acids in a higher ratio will obviously make the green fuel readily meet the critical specifications for biodiesel, especially in conforming to the cold properties of the fuel.